Community empowerment in the production of dry maggots in Dirgantara Village in Yogyakarya - Saputra, Wahyu Nanda Eka; Barida, Muya; Mardhia, Murein Miksa (Universitas Ahmad Dahlan, 2024)
This study examines a community empowerment initiative in Dirgantara Village in Yogyakarta that focuses on producing dry maggots to address challenges in waste management and economic development. The project targets the issue of organic waste by using maggots, specifically the larvae of the Black Soldier Fly, to efficiently decompose organic material. This method not only mitigates environmental pollution but also creates a valuable product that can be sold as animal feed, offering a sustainable income source for the community. The initiative uses a problem-based learning approach, engaging local residents through educational workshops and practical demonstrations to improve their understanding and skills in organic waste management. Results show a significant increase in community members' understanding and awareness of sustainable waste practices. The Dirgantara Village project demonstrates how integrating innovative and sustainable practices can effectively address ecological challenges and enhance economic prospects, serving as a model for other communities facing similar issues.